STRATEGI PENGGUNAAN MEDIA PEMBELAJARAN FLASH CARD UNTUK MENINGKATKAN PEMAHAMAN DAN KETERLIBATAN SISWA PADA MATA PELAJARAN FIKIH KELAS VII - Afifah, Wardah; Manshur, Umar (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
Fiqh learning often faces challenges such as monotonous lecture methods and an unconducive classroom atmosphere, which can lead to student boredom and low engagement. To overcome this, flash card media is used as an innovative learning tool because it can simplify abstract concepts, attract attention, and make the learning process more interactive and enjoyable. This research employs a qualitative descriptive approach in two madrasahs: MTs Nurul Jadid Paiton Probolinggo and MTs Darul Falah Cermee Bondowoso. Data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman's techniques (data reduction, display, and verification). The results indicate that flash cards emerge as a solution to dull learning sessions. This media has proven to increase students' activeness and understanding, especially in recalling fiqh concepts. The strategy involves students directly in the creation and usage of the cards in a flexible and participative manner